Understanding Reduced Gravity Effects on Early Plant Development Before Attempting Life-Support Farming in the Moon and Mars - Medina, F. Javier; Manzano, Aránzazu; Villacampa, Alicia; Ciska, Malgorzata; Herranz, Raúl (Frontiers in Astronomy and Space Sciences, 2021)
Plants are a necessary component of any system of bioregenerative life support for human space exploration. For this purpose, plants must be capable of surviving and adapting to gravity levels different from the Earth gravity, namely microgravity, as it exists on board of spacecrafts orbiting the Earth, and partial-g, as it exists on the surface of the Moon or Mars. Gravity is a fundamental environmental factor for driving plant growth and development through gravitropism. Exposure to real or simulated microgravity produces a stress response in plants, which show cellular alterations and gene expression reprogramming. Partial-g studies have been performed in the International Space Station using centrifuges and in ground based facilities by implementing adaptations in them. Seedlings and cell cultures were used in these studies. The Mars gravity level is capable of stimulating the gravitropic response of the roots and preserving the auxin polar transport. Furthermore, whereas Moon gravity produces alterations comparable, or even stronger than microgravity, the intensity of the alterations found at Mars gravity was milder. An adaptive response has been found in these experiments, showing upregulation of WRKY transcription factors involved in acclimation. This knowledge must be improved by incorporating plants to the coming projects of Moon exploration.